Theorizing about the continuity between waking and dreaming: comment on Domhoff (2017) - Schredl, Michael (Dreaming, 2017)
In his article 'The Invasion of the Concept Snatchers: The Origins, Distortions, and Future of the Continuity Hypothesis,' Domhoff (2017) advocated a cognitive version of the continuity hypothesis. This commentary challenges his claim that his deviations from the original continuity hypothesis formulated by Hall and Nordby (1972) are the only way to advance the theoretical framework of the continuity hypothesis. Furthermore, Domhoff’s concepts are not well operationalized; that is, reliable instruments for measuring the occurrence, intensity, and time frame of personal concerns and preoccupations are lacking. As Domhoff selectively reported the empirical findings that support his notions, the commentary added further research that mostly favors the original version of the continuity hypothesis. The present article pleads for a multiplicity of theoretical and empirical approaches in dream research within the framework of the continuity hypothesis to further our understanding of the relationship between waking life and dreaming. (PsycINFO Database Record (c) 2017 APA, all rights reserved)